Detection of compressive hydrated nucleus pulposus extrusion in dogs with multislice computed tomography. (October 2016) - Royaux, E.; Martlé, V.; Kromhout, K.; Van der Vekens, E.; Broeckx, B.J.G.; Van Ham, L.; Gielen, I.
Highlights: Contrast enhanced computed tomography (CE-CT) was used to characterise hydrated nucleus pulposus extrusion (HNPE) in dogs. HNPE is visualised on CE-CT as a hypodense extradural compressive lesion dorsal to the intervertebral disc space. CE-CT had a sensitivity of 91% and a specificity of 100% for detection of HNPE compared to magnetic resonance imaging. CE-CT is a useful technique for detection of compressive HNPE in dogs. Abstract: Compressive hydrated nucleus pulposus extrusion (HNPE) in dogs is defined as acute extradural compression by hydrated nucleus pulposus material at the level of the associated intervertebral disc. Magnetic resonance imaging (MRI) is the imaging modality of choice for diagnosis of HNPE. The aims of this study were to determine the usefulness of unenhanced computed tomography (CT) and contrast enhanced CT (CE-CT), and the sensitivity and specificity of CE-CT, for detection of compressive HNPE. Using CE-CT, HNPE was visualised as a hypodense extradural compressive lesion with rim enhancement immediately dorsal to the intervertebral disc space, with a sensitivity of 91% and a specificity of 100%. CE-CT is a useful technique to detect compressive HNPE in dogs. However, if no clear lesion is identified with CE-CT, or if additional information about intramedullary changes is required, MRI still needs to be performed.